Exploring the Impact of Family, Social Support, and Health Workers on Reproductive Health Behaviors Among Blind Adolescents in Sukabumi City and Regency - Haryani, Hana; Said, Faridah Mohd; Umar, Nur Syazana (STIKep PPNI Jawa Barat, 2025)
Aims: The purpose of this study is to investigate how family support, social support, and the involvement of health workers affect the reproductive health of blind teenagers in Sukabumi City and Regency. Methods: This study is correlational and uses a cross-sectional technique. The population is made up of 42 teenagers from Sukabumi City and Regency who have visual problems. They were chosen via complete sampling. Multiple linear regression was used to do the statistical analysis. Results: The results demonstrated that the sources of information had a considerable impact on the reproductive health behavior of teenagers with visual difficulties (p-value = 0.000). There was a relationship between knowledge and reproductive health behavior (p-value = 0.000), as well as a connection between attitudes and reproductive health behavior (p-value = 0.000). Furthermore, the reproductive health behaviors of teenagers with visual difficulties were simultaneously influenced by information sources, knowledge, and attitudes (p-value = 0.000). Conclusion: The way teenagers with visual difficulties approach reproductive health is greatly impacted by their sources of information, knowledge, and attitudes. In order to better safeguard and assist teenagers with visual impairments, relevant authorities and the government can use the results of this study as a reference.